2022
DOI: 10.1186/s12889-022-13382-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-participation in a targeted prevention program aimed at lifestyle-related diseases: a questionnaire-based assessment of patient-reported reasons

Abstract: Background Having an unhealthy lifestyle is associated with a higher risk of developing lifestyle-related diseases. Current evidence suggests that interventions targeting health-risk behaviors can help people improve their lifestyles and prevent lifestyle-related diseases. However, preventive programs are often challenged by low participation rates. Reasons for non-participation include lack of time and/or interest, and/or no perceived need for lifestyle intervention. This study explores causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Previous studies on non-participation in lifestyle related-interventions or prevention programs have found that a reason for non-participation is lack of time [ 22 25 ]. This may be due to a busy schedule, where work and the extensiveness of the program may be a barrier [ 25 ]. After participating in this study, a few participants declined further follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on non-participation in lifestyle related-interventions or prevention programs have found that a reason for non-participation is lack of time [ 22 25 ]. This may be due to a busy schedule, where work and the extensiveness of the program may be a barrier [ 25 ]. After participating in this study, a few participants declined further follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited knowledge on non-participation in lifestyle intervention and preventive programs, especially in patients with RA. Previous studies on non-participation in lifestyle related-interventions or prevention programs have found that a reason for non-participation is lack of time [22][23][24][25]. This may be due to a busy schedule, where work and the extensiveness of the program may be a barrier [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several observations can be derived from these studies: Firstly, while focus groups on the conception of these interventions regularly stated a high level of informational need, an increase in disease-specific knowledge was seldom evaluated 12 , 13 , 15 . Secondly, simply providing information material is not sufficient to get participants involved with the topic 14 , 16 , while in comprehensive in-person programs, time investment and travel distance are reasons for non-participation for many potential participants 15 , 17 , 18 . Lastly, observational study designs were used, presumably due to small cohort sizes, and randomized controlled studies evaluating patient education in SSc are lacking.…”
Section: Introductionmentioning
confidence: 99%